Carrying capacity of two official hiking trails, located in Lagoa do Fogo (Azores, Portugal) - Escudero Aznar, Pablo (2012)
I International Conference on Tourism and Sustainability, 22-23 de Setembro de 2011, ISLA Campus Lisboa.